Papillary cystadenoma of the epididymis in a 12-year-old survivor of stage IV neuroblastoma - Nnenaya Agochukwu; Tamara Fitzgerald; Ahmed Khalid Alomari; Emily Christison-Lagay (Elsevier, 2018)
Papillary cystadenoma of the epididymis (PCE) is the second most common benign neoplasm of the epididymis [1]. It is very uncommon and has never been reported in a prepubertal male. It may occur sporadically, but more often occurs in association with von Hippel- Lindau (VHL) disease [2]. There have been over 60 reports of patients with such tumors, with the youngest patient being 16 years old.We present the case of a 12- year old male with a history of stage IV neuroblastoma. He presented with a left paratesticular mass that was discovered on routine follow up physical exam with his pediatric oncologist. He was asymptomatic at the time of presentation with no signs or symptoms of hypoandrogenism. A computed tomography scan of the abdomen and pelvis was negative for lymphadenopathy and additional disease sites. Given the patient's history of stage IV neuroblastoma, there was suspicion of yolk sac tumor or metastases; he underwent an open radical left orchiectomy. Frozen section was consistent with yolk sac tumor, however final pathology revealed normal testicle with PCE.To date, this patient is the youngest reported patient with this diagnosis; furthermore papillary cystadenoma of the epididymis has never been reported in a patient with neuroblastoma. Keywords: Papillary cystadenoma, Epididymis, Prepubertal male, Neuroblastoma